2020
DOI: 10.1186/s12943-020-01281-8
|View full text |Cite
|
Sign up to set email alerts
|

N6-methyladenosine-modified CircRNA-SORE sustains sorafenib resistance in hepatocellular carcinoma by regulating β-catenin signaling

Abstract: Background and aims Accumulating evidence suggests that the primary and acquired resistance of hepatocellular carcinoma (HCC) to sorafenib is mediated by multiple molecular, cellular, and microenvironmental mechanisms. Understanding these mechanisms will enhance the likelihood of effective sorafenib therapy. Methods In vitro and in vivo experiments were performed and clinical samples and online databases were acquired for clinical investigation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
157
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(161 citation statements)
references
References 51 publications
3
157
0
1
Order By: Relevance
“…Xu et al found that CircRNA-SORE plays an important role in it. It can mediate sorafenib resistance in hepatocellular carcinoma by stabilizing YBX1, and N-methylated CircRNA-SORE can also maintain sorafenib resistance through β-catenin signaling 74 , 75 .…”
Section: Circrna and Digestive System Neoplasmsmentioning
confidence: 99%
“…Xu et al found that CircRNA-SORE plays an important role in it. It can mediate sorafenib resistance in hepatocellular carcinoma by stabilizing YBX1, and N-methylated CircRNA-SORE can also maintain sorafenib resistance through β-catenin signaling 74 , 75 .…”
Section: Circrna and Digestive System Neoplasmsmentioning
confidence: 99%
“…However, the m6A-mediated HNF3γ reduction will cause liver cancer cells to be resistant to sorafenib [ 188 ]. Interestingly, m6A modification can stabilize CircRNA-SORE; CircRNA-SORE can act as a miRNA sponge, adsorbing miR-103a-2-5p and miR-660-3p, thereby competitively activating the Wnt/β-catenin pathway and inducing sorafenib resistance [ 189 ]. This shows that the response of m6A modification to drugs may not be single and easy to understand.…”
Section: M6a Modification In Cancer Therapies: Targeted Therapy Chemotherapy Radiotherapy and Immunotherapymentioning
confidence: 99%
“…To this end, some circRNAs were described as associated with drug resistance ( Section 3.2.2 ), and therefore may be relevant as biomarkers in this space [ 99 ]. The mechanism of action in drug resistance has been studied for a number of circRNAs in other types of cancer previously [ 101 , 102 , 103 ], but only a handful of candidates were investigated in detail in BC. One example of a circRNA involved in drug resistance in BC is the above discussed circKDM4C [ 64 ].…”
Section: Clinical Relevance Of Circrnas In Bcmentioning
confidence: 99%